2010
DOI: 10.1016/j.jbiomech.2010.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of immature articular cartilage compressive moduli and Poisson’s ratios by in vitro stimulation with IGF-1 and TGF-β1

Abstract: Mechanisms of articular cartilage growth and maturation have been elucidated by studying composition-function dynamics during in vivo development and in vitro culture with stimuli such as insulin-like growth factor-1 (IGF-1) and transforming growth factor-beta 1 (TGF-β1). This study tested the hypothesis that IGF-1 and TGF-β1 regulate immature cartilage compressive moduli and Poisson's ratios in a manner consistent with known effects on tensile properties. Bovine calf articular cartilage from superficial-artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(56 citation statements)
references
References 38 publications
4
52
0
Order By: Relevance
“…In AC, PG swelling stress is restrained by the collagen network and helps to resist compressive forces in vivo. Studies have shown that the immature and mature AC equilibrium aggregate modulus ( ) and AC compressive modulus ( ) may initially decrease then increase with increasing compressive strains (Ficklin et al 2001;Wang et al 2003;Williams et al 2010). Therefore, for this study it is hypothesized that for large compressive strains (>15% -45%) the COL network should no longer be in tension in the direction of the loading axis after reaching a sufficient compressive strain (>15% -45%).…”
Section: Goalsmentioning
confidence: 96%
See 3 more Smart Citations
“…In AC, PG swelling stress is restrained by the collagen network and helps to resist compressive forces in vivo. Studies have shown that the immature and mature AC equilibrium aggregate modulus ( ) and AC compressive modulus ( ) may initially decrease then increase with increasing compressive strains (Ficklin et al 2001;Wang et al 2003;Williams et al 2010). Therefore, for this study it is hypothesized that for large compressive strains (>15% -45%) the COL network should no longer be in tension in the direction of the loading axis after reaching a sufficient compressive strain (>15% -45%).…”
Section: Goalsmentioning
confidence: 96%
“…Additionally the mechanical properties, tissue structure, and tissue composition of AC have been shown to vary with depth from the articular surface Williams et al 2010). AC is composed primarily of proteoglycan (PG) molecules and a collagen (COL) fibril network.…”
Section: Table Of Contentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin-like growth factor 1 (IGF1) and insulin-like growth factor binding protein 6 (IGFBP6) have known roles in articular cartilage homeostasis. IGF1 is important in the regulation of normal articular cartilage growth and development through its capacity to stimulate proteoglycan synthesis, promote chondrocyte survival, and oppose the activities of catabolic cytokines (60,70). IGF1 action was shown to be modulated by IGF-binding proteins (IGFBP-1-6) (16).…”
Section: Biological Functions and Canonical Pathways Of De Genesmentioning
confidence: 99%